JUAL BELI TANAH ANTARA AHLI WARIS ALMARHUMAH HADIDJAH DENGAN ALMARHUM SOPYAN SYAHRONI (STUDI KASUS PUTUSAN NO. 8/PDT.G/2018/PN.BDG) : Land Sale and Purchase Between the Heirs of Almarhum Hadidjah with Almarhum Sopyan Syahroni (Case Study of Decision No. 8/Pdt.G/2018/PN.Bdg) - Salsabila Prajna Damayanti; Novina Sri Indiraharti (Faculty of Law, Universitas Trisakti, 2024)
Sale and purchase is a legal act of transfer rights that is clear, cash, and real, there was sale and purchase of land between the heirs of the late Hadidjah and the late Sopyan Syahroni. It turned out that the seller certified and sold it to a third party. The main issue is whether the sale and purchase between the Heirs of Almh. Hadidjah with the late Sopyan Syahroni is valid according to the law. Even though the formal requirements and the orderly administration of land registration do not necessarily make the sale and purchase invalid, because the sale and purchase is considered valid if it has fulfilled the requirements of cash, light, and real based on customary law and the panel of judges has been correct in deciding the party entitled to the disputed land based on the publication system of land registration in Indonesia, namely a negative publication system that contains positive elements where because the heirs of Alm. Sopyan Syahroni could prove that they were the rightful landowners, Rudi Sanjaya and H. Toat as the last landowners lost their rights despite having bought in good faith.